Atomic diffusion behavior in Cu-Al explosive welding process - Liu, K. X. (2013)
A hybrid method is proposed to study atomic diffusion behavior in Cu-Al explosive welding process. The method combines molecular dynamics simulation and classical diffusion theory. Cu-Al explosive welding and scanning electron microscope experiments are done to verify the method. Using the method, we find that the atomic diffusion mostly takes place in the unloading stage of the welding process. The diffusion coefficients are collision velocity-dependent, with higher velocities generating larger coefficients. When there is no transverse velocity, the diffusion coefficient is directly proportional to the longitudinal velocity. With the longitudinal velocity fixed, the diffusion coefficient is proportional to the square of the transverse velocity. The thickness of the diffusion layer is calculated from the simulation result, and it is in good agreement with the experiment result.